2006
DOI: 10.1590/s0103-97332006000600066
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural studies on SnS films grown by co-evaporation

Abstract: Polycrystalline SnS thin films were grown on glass substrates using a novel procedure involving a chemical reaction between the precursor species evaporated simultaneously. This is a relatively new material, which exhibits excellent properties to be used as absorbent layer in solar cells. X-ray diffraction (XRD) measurements indicate that the synthesized samples grow in several phases (SnS, SnS 2 and Sn 2 S 3 ) depending upon the deposition conditions. However, through an exhaustive parameter study, conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 6 publications
11
23
0
Order By: Relevance
“…Thus, it can be concluded that these SnS films were a reasonably homogeneous preparation. The values of refractive index were found to be 1.7, which is to be compared with the refractive index of other amorphous SnS films estimated from transmission and reflection spectra, found to be between 3 and 4.5 at wavelength range from 600 nm to 1100 nm as reported by Yue et al [4] and Cifuentes et al [22] The difference in these values may be due to differences in the properties of the structure of our sample, which revealed the amorphous structure, and method of preparation. The value of the refractive index of our SnS film is within the scope of glass b2, which can be considered as a new kind of visual material of a thin layer [23].…”
Section: Discussionsupporting
confidence: 68%
“…Thus, it can be concluded that these SnS films were a reasonably homogeneous preparation. The values of refractive index were found to be 1.7, which is to be compared with the refractive index of other amorphous SnS films estimated from transmission and reflection spectra, found to be between 3 and 4.5 at wavelength range from 600 nm to 1100 nm as reported by Yue et al [4] and Cifuentes et al [22] The difference in these values may be due to differences in the properties of the structure of our sample, which revealed the amorphous structure, and method of preparation. The value of the refractive index of our SnS film is within the scope of glass b2, which can be considered as a new kind of visual material of a thin layer [23].…”
Section: Discussionsupporting
confidence: 68%
“…The low values of the transmittance obtained in this work is close to that reported by Cifuentes et al 16) All the films had an absorption coefficient, > 10 4 cm À1 and the evaluated energy band gap varied in the range, 1.3-1.34 eV with the increase of substrate temperature T s . The sharpness of the fall in the fundamental edge without the existence of shoulders confirms that there are no other phases present in the films.…”
Section: Optical Analysissupporting
confidence: 90%
“…Tin Sulfide is a unique important binary semiconductor material of IV-VI exhibiting p and n type behaviour, with direct and indirect band gaps of 1.3 and 1.09 eV, respectively, which is close to the ideal band gap 1.5 eV with highest photovoltaic conversion efficiency (Xu et al 2012;Sohila et al 2011;Hickey et al 2008). It has been reported to have optical absorption coefficient (> 10 4 cm −1 ) and conductivity (hole mobility = 90 cm 2 V −1 s −1 ) in single crystals, across the near-infrared and visible spectrum which coincide with the maximum efficiency for optimum band gap according to Shockley-Queisser limit within the AM 1.5 solar spectrum (Cifuentes et al 2006;Greyson et al 2006;Tanusevski 2003;Baig et al 2018).…”
Section: Introductionsupporting
confidence: 67%